An investigation into the microstructural evolution and shrinkage control in internally cured mortars with milkweed fibres - Amirmohammad Sabziparvar; M. Reza Foruzanmehr (Case Studies in Construction Materials)
This study presented a significant advancement in the use of Milkweed (MW) fibres as internal curing agents in low water-to-cement (w/c) cementitious materials. The research focused on how different pre-treated MW fibres, with different composition, can impact internal curing efficacy in reducing autogenous shrinkage of cement mortars. In addition, the hydration behaviour and microstructural development were revealed using a series of tests including setting time, compressive strength, flexural strength, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA/DTG). A key finding of this study is the remarkable reduction in autogenous shrinkage, with using 0.1 % wt. pre-treated MW fibres leading to up to 28 % reduction at 7 days, compared to plain mortars. Furthermore, internal curing effect resulted in narrowing the compressive strength gap between the reference mixes and those with pre-treated MW fibres in the later stages of hydration. It was also found that the removal of hemicellulose through hybrid treatment can reduce the delay in the final setting time of cement from 45 minutes to 18 minutes. Additionally, while the incorporation of N- and HT-treated MW fibres had negligible effects on drying shrinkage, the inclusion of HY-treated MW fibres led to a 15 % increase in drying shrinkage at 7 days. This difference in behaviour was attributed to the presence of lignin in N- and HT-treated fibres. Lignin was found to play a crucial role in influencing the drying shrinkage, microstructural development, and mechanical properties of MW fibre-incorporated cementitious mixes. Acting as a protective barrier, lignin shielded the MW fibres from cement infiltration into their lumina. Moreover, it served as both a physical and chemical barrier, reducing moisture transport through the capillary network during drying. In conclusion, this study demonstrated the potential of using pre-treated MW fibres as internal curing agents to effectively reduce autogenous shrinkage, with minimal compromise in terms of the compressive strength of cementitious composites.